Penerapan Metode LSQ (Learning Start With Question) dalam Upaya Meningkatkan Hasil Belajar Siswa - Shofwatal Qolbiyyah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This study aims to determine the application of the LSQ (Learning Start with Question) method in an effort to improve student learning outcomes. The research is a qualitative descriptive study, taking the library background of Darul ‘Ulum Jombang University. Data collection is done by tracing the literature related to the subject matter of the research. Data analysis is done by giving meaning to the data that was successfully collected through descriptive analysis techniques. The results of the study show that the activeness of the teacher in the ability to create an atmosphere still needs to be improved, and the LSQ (Learning Start with Question) method is needed, so that students who are not familiar with the learning conditions using the LSQ method will feel accustomed and enthusiastic in the learning process teaching takes place, and ultimately student learning outcomes can also increase.